Historical understanding and rethinking the foundations - Roux, Jurie le (HTS teologiese studies, 2007)
This article contributes to the fundamental rethinking of New Testament scholarship being undertaken by New Testament scholars attached to the University of South Africa (UNISA), Pretoria, South Africa. The thrust of the article holds that the historical Jesus research is of the utmost importance and it puts the emphasis on the individuality of an event and the contribution of nineteenth century reflection on history. As point of departure and further elaboration it accentuates the notion that history writing must be a form of homecoming.